Law No. 213 of the year 2017 on issuing the law on labour trade union organizations and the protection of the union organization rights = قانون المنظمات النقابية العمالية. (2025)
1. Definitions and general provisions -- 2. The establishment of the trade union organizations and objectives thereof -- 3. Membership of the labour trade union organization -- 4. Formations of the labour trade union organizations -- 5. Conditions and procedures of running for election and election to the membership of the board of directors of the labour trade union organization -- 6. Rights and guarantees of exercising the trade union Work -- 7. Resources and funds of the labour trade union organization and control thereof -- 8. Exemptions and benefits of the trade union organizations -- 9. The articles of association and financial regulations of the trade union organizations -- 10. Penalties